PERSAMAAN DAN PERBEDAAN ANTARA SANKSI HUKUM ISLAM DAN HUKUM POSITIF TENTANG SANKSI HUKUM TERHADAP PELAKU ABORTUS - adnan, Latifah (Media Akademika, 2016)
Both positive law and Islamic law considers absortion as a despicableÂ act, becauseÂ it is opposen to moral and ethical. And the perpetrators of such actsÂ are entitled to legal sanctions as aÂ result if indecency that they did. This study discusses the legalÂ punishment of abortus provocatus according to the concept of Imam Maliki and Imam SyafiâI. In the opinion of Imam MalikiÂ and Imam Syafiâi, those who perform abortion intentionally (abortus provocatus) subject to two legal sanctions, namely diyat law sanctions (fines) and kifarat law sanctions.